Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1186/1471-2164-7-118
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of lymphoblastoid cell lines from monozygotic twins discordant in severity of autism reveals differential regulation of neurologically relevant genes

Abstract: Background: The autism spectrum encompasses a set of complex multigenic developmental disorders that severely impact the development of language, non-verbal communication, and social skills, and are associated with odd, stereotyped, repetitive behavior and restricted interests. To date, diagnosis of these neurologically based disorders relies predominantly upon behavioral observations often prompted by delayed speech or aberrant behavior, and there are no known genes that can serve as definitive biomarkers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(164 citation statements)
references
References 77 publications
5
156
0
2
Order By: Relevance
“…They used microarray analysis to observe lymphoblastoid cell lines derived from the blood of MZ twins for biomarkers of autism with the hypothesis that expression differences between affected and unaffected individuals might be present in tissues besides the brain [63]. Based on their results, they were able to show that MZ twins discordant for ASD exhibited differential expression for genes critical in the nervous system.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…They used microarray analysis to observe lymphoblastoid cell lines derived from the blood of MZ twins for biomarkers of autism with the hypothesis that expression differences between affected and unaffected individuals might be present in tissues besides the brain [63]. Based on their results, they were able to show that MZ twins discordant for ASD exhibited differential expression for genes critical in the nervous system.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…In a study by Hu et al [63], the authors studied differences in gene expression in genetically identical individuals with different degrees of autism. They used microarray analysis to observe lymphoblastoid cell lines derived from the blood of MZ twins for biomarkers of autism with the hypothesis that expression differences between affected and unaffected individuals might be present in tissues besides the brain [63].…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Following studies showing RNA and microRNA expression differences in lymphoblastoid cell lines from 3 MZ pairs discordant for ASD symptoms, which identified known ASD-associated genes [74,75], Wong et al [76] performed a discordant twin EWAS with a difference. In addition to analysing genome-scale methylation in whole blood from 10 ASD-discordant MZ pairs, they also studied MZ pairs discordant for the ASD-related phenotypes of social autistic traits (n = 9), autistic restricted repetitive behaviours and interests (n = 8) and communication autistic traits (n = 8), together with a case-control analysis in 100 individuals.…”
Section: Ewas Of Disease-discordant Mz Twinsmentioning
confidence: 99%
“…Future research in this domain could potentially implicate oxidative stress as a biomarker for ASD, thus contributing to the literature of specific risk factors which may play a role in the ASD clinical presentation. In addition to oxidative stress being proposed as a biomarker for ASD, DNA microarray analysis has been investigated as a means to investigate candidate genes that may be implicated in inflammation in ASD (Hu et al 2006). Studies of differential gene expression among genetically identical twins with ASD suggested that differential gene expression in lymphoblastoid cell lines (LCL), which transformed cell lines generated from peripheral blood lymphocytes by infection with Epstein-Barr Virus (EBV), could serve as easily accessible biomarkers for ASD diagnoses by expressing a defined percentage of the genes that are typically found within ASD (Hu et al 2006).…”
Section: Inflammation As a Potential Biomarkermentioning
confidence: 99%